Database Sharding for Increased Scalability and Performance in Data-Heavy Applications - Jayaraman, Srinivasan; Jain, Aayush (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Database sharding is a critical technique used to enhance the scalability and performance of data-intensive applications by distributing data across multiple servers, or "shards." This approach helps address the challenges associated with managing large volumes of data, improving query response times, and ensuring system reliability. As data-heavy applications continue to grow, sharding offers an efficient solution for minimizing the strain on a single database server, which often leads to performance bottlenecks. By partitioning the database into smaller, more manageable pieces, sharding allows for parallel processing, load balancing, and more efficient use of resources. This, in turn, supports higher availability, fault tolerance, and better management of high traffic and heavy workloads. The process of sharding involves determining an appropriate key to split data across shards, ensuring that each shard holds a subset of the data. Sharding strategies, such as horizontal and vertical partitioning, can be employed depending on the specific needs of the application. While sharding improves performance, it also introduces complexity in terms of data consistency, transaction management, and query processing across multiple shards. Thus, it is essential to implement robust techniques for managing distributed transactions, replication, and synchronization to avoid issues like data inconsistency. This paper explores the principles of database sharding, its advantages, challenges, and best practices for implementing it in data-heavy applications. By leveraging sharding effectively, organizations can achieve improved performance and scalability while maintaining data integrity across distributed systems.